PURSUING LIFE'S JOYS as an IT Developer. - Yi Ji-young (Koreana)
The article profiles Embedded software developer Kim Yoon-ki and his experience at work. Topics discussed include a brief profile of Yoon-ki, the primary concept of overtime in organizations, the significance of happiness, stress at work, the continuous development in information technology, and the work attitude.